2017
DOI: 10.1038/mp.2017.1
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Otx2 mis-localization delays critical period plasticity across brain regions

Abstract: Accumulation of non-cell autonomous Otx2 homeoprotein in postnatal mouse visual cortex (V1) has been implicated in both the onset and closure of critical period plasticity. Here, we show that a genetic point mutation in the glycosaminoglycan-recognition motif of Otx2 broadly delays the maturation of pivotal parvalbumin-positive (PV+) interneurons not only in V1 but also in the primary auditory (A1) and medial prefrontal cortex (mPFC). Consequently, not only visual, but also auditory plasticity is delayed, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 64 publications
7
99
0
Order By: Relevance
“…The PNN accumulates postnatally to reach adult density at P50 in the V1 area of the mouse visual cortex (Ye et al, 2018;Lee et al, 2017;Lensjø et al, 2017b). In order to test the hypothesis that targeted chemogenetic inhibition of PV interneurons alters adult PNN density, we adapted the protocol known to reinstate visual plasticity at P35 (Kuhlman et al, 2013) to measure PNN changes between P58 and P61 (see Methods and Fig.S1).…”
Section: Targeted Chemogenetic Inhibition Of Pv Interneurons Induces mentioning
confidence: 99%
“…The PNN accumulates postnatally to reach adult density at P50 in the V1 area of the mouse visual cortex (Ye et al, 2018;Lee et al, 2017;Lensjø et al, 2017b). In order to test the hypothesis that targeted chemogenetic inhibition of PV interneurons alters adult PNN density, we adapted the protocol known to reinstate visual plasticity at P35 (Kuhlman et al, 2013) to measure PNN changes between P58 and P61 (see Methods and Fig.S1).…”
Section: Targeted Chemogenetic Inhibition Of Pv Interneurons Induces mentioning
confidence: 99%
“…During mouse late postnatal development, the privileged accumulation of OTX2 within FSPV cells in the visual cortex opens plasticity for binocular vision at P20 and closes it by P40 (17). This critical period of plasticity is thus regulated by non-cell autonomous OTX2, a phenomenon that was recently extended to the auditory cortex and medial prefrontal cortex (mPFC) (18). For the visual cortex, it was also shown that pharmacological or genetic decreases of FSPV cell OTX2 content in the adult cortex reopens a window of plasticity, allowing for the recovery of binocular vision in mice made amblyopic by the closure of one eye during the juvenile critical period (14; 15).…”
Section: Introductionmentioning
confidence: 99%
“…6 Although these trajectories appear to be distinct, recent evidence suggests that transient, stress-induced perturbations in transcriptional programs during sensitive periods may influence susceptibility to later life stressors 7 or prolong the sensitive period altogether. 8 It is likely that both early and later life stress may exert lasting negative influences on transcription, cell functioning and behavior, through common epigenetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%